Erratum: Dielectric and piezoelectric properties of textured Sr0.53Ba0.47Nb2O6 ceramics prepared by templated grain growth (Journal of Materials Research (September 2002) 17:9) - Duran, Cihangir; Trolier-Mckinstry, Susan E.; Messing, G. L. (My University, 2003)
[No abstract available]